English teaching method training to improve the competency of kindergarten teachers - Rizkiana Maharddhika; Mushoffan Prasetianto; Hafida Ruminar; Dian Islami Prasetyaningrum (University of Merdeka Malang, 2023)
The English Teaching Methods training program as a Community Service activity was carried out at one of the kindergarten schools, in Malang city. This training aims to improve the professionalism of kindergarten Teachers in teaching English materials. This activity consists of several stages namely preliminary study, material preparation, onsite training, and evaluation. The preliminary study, which involved discussion with presenters and school principals, was conducted to identify problems and assess teachers' needs. During the training process, teachers are equipped with theoretical frameworks, methodological examples, and English teaching materials specifically tailored for the effective instruction of young learners. Subsequently, the educators were allocated a period for discussion, during which they engaged in the development of inventive approaches and media. These outputs were subsequently delivered on the next day. The training instructors also offered feedback for every new method and media creation that was presented by the teachers. Upon the end of the training program, the participants offered testimonials and suggested ideas pertaining to the training. In addition, the lecturers offered instructional objects that can be utilized when teaching English in kindergarten.